Educating in Human Rights for Children through Picture Books - Díaz-Seoane, Ángeles; Ferreira-Boo, Carmen; Mesías-Lema, José María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The purpose of this paper is the development of critical thinking and civic attitude based on human rights for childhood using the picturebook reading. In doing so, the nexus between textual and visual language of the album and its use to develop literary, plastic and values education are analysed. Four titles were selected and analysed to carry out educational mediation in early childhood education related to human rights, to conclude that the picturebook is an ideal pedagogical tool to promote literary reading, visual literacy and the creation of a future critical, empathetic and conscious citizenship of human rightsin English.